2006
DOI: 10.1128/mcb.26.10.3976-3985.2006
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling the Pleiotropic Phenotypes of clk-1 with tRNA Missense Suppressors in Caenorhabditis elegans

Abstract: clk-1 encodes a demethoxyubiquinone (DMQ) hydroxylase that is necessary for ubiquinone biosynthesis. When Caenorhabditis elegans clk-1 mutants are grown on bacteria that synthesize ubiquinone (UQ), they are viable but have a pleiotropic phenotype that includes slowed development, behaviors, and aging. However, when grown on UQ-deficient bacteria, the mutants arrest development transiently before growing up to become sterile adults. We identified nine suppressors of the missense mutation clk-1(e2519), which har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…Thus, it appears that MCLK1 has an additional function that is unrelated to UQ biosynthesis but responsible for the phenotypes observed in young Mclk1 ϩ/Ϫ mutants. This is consistent with several results from nematodes which also strongly suggest that CLK-1 has other functions (24,25).…”
supporting
confidence: 93%
“…Thus, it appears that MCLK1 has an additional function that is unrelated to UQ biosynthesis but responsible for the phenotypes observed in young Mclk1 ϩ/Ϫ mutants. This is consistent with several results from nematodes which also strongly suggest that CLK-1 has other functions (24,25).…”
supporting
confidence: 93%
“…In particular, it was found that both the phenotypically severe allele clk-1(qm30), a partial deletion that does not produce any CLK-1 protein, and the phenotypically weaker allele clk-1(e2519), a Glu to Lys missense mutation that produces wild-type levels of a full-length mutant protein (11), are equally unable to sustain UQ biosynthesis (12). Furthermore, suppression of clk-1(e2519) by a tRNA missense suppressor produces only very small amounts of UQ 9 but results in full phenotypic suppression (13). Together these observations suggest that at least part of the phenotype of clk-1 mutants is not because of the defect in UQ biosynthesis.…”
Section: Mutational Inactivation Of Clk-1 In Caenorhabditis Elegansmentioning
confidence: 89%
“…However, several lines of evidence argue against CoQ depletion accounting for the effects of statins on mitochondria: (i) supplying CoQ to C. elegans conferred no protection from the toxic effects of statins (CoQ 10 was tested at 50 μg/mL and concentrations of CoQ 9 ranging from 10 to 80 μg/mL were tested, all without effect); (ii) the atfs-1(et15) mutant is not resistant to rotenone, antimycin A, or sodium azide, which are inhibitors of the mitochondrial respiratory chain (25,26) (Fig. S7 B-D); and (iii) it is well known that CoQ is dietarily available to C. elegans that are fed Escherichia coli as in our experiments (27,28) and that very little endogenous CoQ is sufficient for a wild-type phenotype even in the absence of dietary CoQ (29).…”
Section: Effects Of Statins On Mitochondria Are Not Related To Inhibimentioning
confidence: 99%